Optical Control of Peroxisomal Trafficking - Spiltoir, Jessica I. (ACS Synth Biol, 2015)
[Image: see text] The blue-light-responsive LOV2 domain of Avena sativa phototropin1 (AsLOV2) has been used to regulate activity and binding of diverse protein targets with light. Here, we used AsLOV2 to photocage a peroxisomal targeting sequence, allowing light regulation of peroxisomal protein import. We generated a protein tag, LOV-PTS1, that can be appended to proteins of interest to direct their import to the peroxisome with light. This method provides a means to inducibly trigger peroxisomal protein trafficking in specific cells at user-defined times.